2015
DOI: 10.1007/s00216-015-8765-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescent DNA sensor based on controlled Zn-mediated grafting of diazonium precursors

Abstract: Controlled Zn-mediated grafting of a thin layer of a diazonium salt was used to functionalise a carbon electrode with ruthenium(II)-tris-bipyridine (Ru)-labelled DNA for use as a capture probe in an electrochemiluminescent genosensor. A secondary reporter probe was labelled with a ferrocene (Fc) molecule, and in the presence of the single-stranded DNA target a genocomplex formed, where the Fc-label effectively quenched the electrochemiluminescence of the signal emitted from the Ru-label. The spacing of the lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Aryldiazonium cations can be easily reduced into the corresponding aryl radicals by loss of nitrogen, and these very reactive aryl radicals are able to react with a surface, forming a strong surface–carbon bond. The aryl radicals can be produced by electrochemical reduction at conducting substrates, by chemical reduction with the use of reducing agents such as H 3 PO 2 , ascorbic acid, or metals such as zinc or iron, combined with sulfuric or hydrochloric acid, as well as by photochemical reduction in the presence of a sensitizer . Spontaneous reactions with the surface involving solvent-induced homolytic dediazonation , or aqueous acidic solution for gold modification, or involving the substrate itself in the case of reducing metals such as copper, , iron, and nickel, have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…Aryldiazonium cations can be easily reduced into the corresponding aryl radicals by loss of nitrogen, and these very reactive aryl radicals are able to react with a surface, forming a strong surface–carbon bond. The aryl radicals can be produced by electrochemical reduction at conducting substrates, by chemical reduction with the use of reducing agents such as H 3 PO 2 , ascorbic acid, or metals such as zinc or iron, combined with sulfuric or hydrochloric acid, as well as by photochemical reduction in the presence of a sensitizer . Spontaneous reactions with the surface involving solvent-induced homolytic dediazonation , or aqueous acidic solution for gold modification, or involving the substrate itself in the case of reducing metals such as copper, , iron, and nickel, have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…Liu found that the diazo-derived monolayer on the carbon electrode is more stable than the alkanethiol self-assembled monolayer on gold (Khli et al 2013). A stable coupling agent ensures that the biomolecules adhere rmly to the electrode and ensures the accuracy of the subsequent analytical steps (Torréns et al 2015).…”
Section: )mentioning
confidence: 99%
“…A similar approach was followed by Ortiz et al to attach a biotin-Rubpy-DNA capture probe for the implementation of an electrochemiluminescent labelled DNA sensor. 61 In this case, an original 3,5-bis(4-diazophenoxy) benzoic acid platform was grafted via Zn-mediated reduction on glassy carbon, followed by the streptavidin intermediate coupling. This functionalization method, which was recently reported by the group, 62 allowed to generate thinner layers than those obtained by electroreduction, and led to similar postfunctionalization yield using EDC/NHS coupling.…”
Section: Metal Cation Sensorsmentioning
confidence: 99%
“…Carbon 114 -Gold, 165 Gold, 20,336 carbon 21,300 ORR, 20 biofuel cells, 21 sugar sensing 300 Non enzymatic proteins (including peptides, amino acids and analogues) Amide coupling Carbon, 10,11,39,42,44,61,73,325,337,338 graphite-epoxy composite 13 gold, 9,10,12,[34][35][36]40,47 SWCNT, 53 Fe-core/cabon-shell NPs, 57 graphene, 54,339 AgNPs/SiO2/GO hybrid, 55 ITO, 37 boron-doped carbon nanowall 340 Immunosensing, 35- Nucleic acids (DNA, aptamers) Amide coupling Gold, 58,66,68 carbon, 59,63,64,344 graphene, 67,334 SPCE, pencil graphite electrode 65 Sensing, 334 DNA and protein detection, 58 DNA biosensing, 59,…”
mentioning
confidence: 99%